A comparison of gonadotropin-releasing hormone and human chorionic gonadotropin in dairy cows with ovarian follicular cysts - Kesler, Kathryn; Longcore, Grace; Russell, Alex (Veterinary Evidence, 2022)
PICO question In adult dairy cows with ovarian follicular cysts, does treatment with gonadotropin-releasing hormone (GnRH) compared to human chorionic gonadotropin (hCG) result in a more rapid return to cyclicity? Clinical bottom line Category of research question Treatment The number and type of study designs reviewed The publications consisted of six non-blinded randomised comparative or controlled trials Strength of evidence Weak Outcomes reported Recovery time, clinical cure, and interval to conception were consistently evaluated. Many studies also evaluated other fertility parameters such as first estrus or first treatment conception, overall pregnancy and conception risks, and breedings per conception Conclusion At this time, there is insufficient evidence to suggest whether GnRH or hCG is more efficacious for treating ovarian follicular cysts in dairy cattle. Ultimately, further research is essential to elucidate which treatment results in a more rapid return to cyclicity for dairy cattle afflicted with cystic ovarian follicles How to apply this evidence in practice The application of evidence into practice should take into account multiple factors, not limited to: individual clinical expertise, patient’s circumstances and owners’ values, country, location or clinic where you work, the individual case in front of you, the availability of therapies and resources. Knowledge Summaries are a resource to help reinforce or inform decision making. They do not override the responsibility or judgement of the practitioner to do what is best for the animal in their care.